Supporting family caregivers in the transition between hospital and their relative's preferred place for end of life care. Issue 3 (1st September 2016) - Campling, Natasha; Duke, Sue; Firth, Pam; Lund, Susi; Lunt, Neil; May, Carl; Richardson, Alison
Abstract : Introduction: A recent national survey of carers found that only half of family carers providing end of life care received the support they needed and this support was less likely to be provided in hospital. 1 Similarly, a study of discharge in older adults found that most family caregivers are not involved in discharge decisions. 2 Aims: This study aims to understand and support family in the work they do to facilitate end of life discharge. The study objectives are to: Design and assess the usability of the intervention for family members supporting a person being transferred from hospital to their preferred place for end of life care. Implement the intervention in hospital practice to reveal the factors that promote and inhibit implementation of the intervention; and develop toolkits to facilitate transfer of the intervention between settings. Methods: The intervention integrates tested support components (reduction of uncertainty, information provision and coaching) within the framework of Family Sense of Cohesion Theory, to promote family resilience and, thereby, facilitate effective 24/7 care. The intervention has been clinically modelled with practitioners as conversational prompts, each addressing an intervention component (meaningfulness, uncertainty, comprehensibility and manageability). Using Participatory Learning and Action (PLA) methodology the study will be conducted in five developmental cycles. Results: The intervention will be piloted at three clinical sites from July 2016. Following this, there will be further roll out to 7 additional sites across England (through to September 2017). References: National Council for Palliative Care.Who Cares? Support for carers of people approaching the end of life. London: The National Council for Palliative Care; 2013 Waring J, Marshall F, Bishop S, et al . An ethnographic study of knowledge sharing across the boundaries between care processes, services and organisations: the contribution to 'safe' hospital discharge. Health Services and Delivery Research 2014;2 (29)